Pharmacological Protein Kinase C Modulators Reveal a Pro-hypertrophic Role for Novel Protein Kinase C Isoforms in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Pohjolainen, Lotta; Easton, Julia; Solanki, Reesha; Ruskoaho, Heikki; Talman, Virpi (Frontiers in Pharmacology, 2021)
Background: Hypertrophy of cardiomyocytes (CMs) is initially a compensatory mechanism to cardiac overload, but when prolonged, it leads to maladaptive myocardial remodeling, impairing cardiac function and causing heart failure. A key signaling molecule involved in cardiac hypertrophy is protein kinase C (PKC). However, the role of different PKC isoforms in mediating the hypertrophic response remains controversial. Both classical (cPKC) and novel (nPKC) isoforms have been suggested to play a critical role in rodents, whereas the role of PKC in hypertrophy of human CMs remains to be determined. Here, we aimed to investigate the effects of two different types of PKC activators, the isophthalate derivative HMI-1b11 and bryostatin-1, on CM hypertrophy and to elucidate the role of cPKCs and nPKCs in endothelin-1 (ET-1)-induced hypertrophy in vitro. Methods and Results: We used neonatal rat ventricular myocytes (NRVMs) and human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to study the effects of pharmacological PKC modulators and ET-1. We used quantitative reverse transcription PCR to quantify hypertrophic gene expression and high-content analysis (HCA) to investigate CM morphology. In both cell types, ET-1, PKC activation (bryostatin-1 and HMI-1b11) and inhibition of cPKCs (Gö6976) increased hypertrophic gene expression. In NRVMs, these treatments also induced a hypertrophic phenotype as measured by increased recognition, intensity and area of α-actinin and F-actin fibers. Inhibition of all PKC isoforms with Gö6983 inhibited PKC agonist-induced hypertrophy, but could not fully block ET-1-induced hypertrophy. The mitogen-activated kinase kinase 1/2 inhibitor U0126 inhibited PKC agonist-induced hypertrophy fully and ET-1-induced hypertrophy partially. While ET-1 induced a clear increase in the percentage of pro-B-type natriuretic peptide-positive hiPSC-CMs, none of the phenotypic parameters used in HCA directly correlated with gene expression changes or with phenotypic changes observed in NRVMs. Conclusions: This work shows similar hypertrophic responses to PKC modulators in NRVMs and hiPSC-CMs. Pharmacological PKC activation induces CM hypertrophy via activation of novel PKC isoforms. This pro-hypertrophic effect of PKC activators should be considered when developing PKC-targeted compounds for e.g. cancer or Alzheimer’s disease. Furthermore, this study provides further evidence on distinct PKC-independent mechanisms of ET-1-induced hypertrophy both in NRVMs and hiPSC-CMs.